From Pleasure to Pain, and Back Again: The Intricate Relationship Between Alcohol and Nociception - Robins, Meridith T (Alcohol Alcohol, 2019)
AIMS: A close and bidirectional relationship between alcohol consumption and pain has been previously reported and discussed in influential reviews. The goal of the present narrative review is to provide an update on the developments in this field in order to guide future research objectives. METHODS: We evaluated both epidemiological and neurobiological literature interrogating the relationship between alcohol use and pain for the presence of significant effects. We outlined studies on interactions between alcohol use and pain using both self-reports and objective experimental measures and discussed potential underlying mechanisms of these interactions. RESULTS: Epidemiological, preclinical and clinical literature point to three major interactions between alcohol use and pain: (a) alcohol use leading to hyperalgesia, (b) alcohol use moderating pain and hyperalgesia and (c) chronic pain as a risk factor predisposing to alcohol relapse. Neurobiological studies using animal models to assess these interactions have transitioned from mostly involuntary modes of experimenter-controlled alcohol administration to self-administration procedures, and increasingly indicate that neuronal circuits implicated in both withdrawal and anticipation stages of alcohol use disorder also have a role in chronic pain. Mechanistically, alterations in GABA, glutamate, the corticotropin-releasing factor system, endogenous opioids and protein kinase C appear to play crucial roles in this maladaptive overlap. CONCLUSIONS: Many of the principles explaining the interactions between alcohol and pain remain on a strong foundation, but continuing progress in modeling these interactions and underlying systems will provide a clearer basis for understanding, and ultimately treating, the damaging aspects of this interaction.